From Watching To Purchasing: The Influence Of It Affordance Dimensions On Live Streaming Marketplace - Evi Yulianti; Hasnawati Hasnawati (Jurnal Indonesia Sosial Teknologi, 2024)
Live streaming marketplaces are currently growing rapidly and make it easier for various parties to interact, shop, and promote products in real-time. This study examines the influence of factors in IT Affordance (Visibility, Metavocing, Guidance Shopping, Trading Affordance, Triggered Attending, and Interactivity) on Immersion directly and on Actual Purchase indirectly on live streaming media on the marketplace. This research data was obtained using a questionnaire in the form of a google form and disseminated through WhatsApp and other social media networks such as Instagram and Twitter or X and as many as 183 google forms have been filled. All answers are eligible for processing. The results of this study show that Metavocing, Trading Affordance, Triggered Attending, and Interactivity have a positive effect on Immersion, while Visibility and Guidance shopping have no effect on Immersion, and Immersion has a positive effect on Immersion. Actual Purchase. However, all variables in IT Affordance (Visibility, Metavocing, Guidance shopping, Trading Affordance, Triggered Attending, and Interactivity) have no indirect effect on  the Actual Purchase mediated by Immersion